Marcus inverted region in the photoinduced electron transfer reactions of ruthenium(ii)-polypyridine complexes with phenolate ions. - Verma, Smriti; Tripathi, P N; Singh, Rajesh P (International Multidisciplinary Research Journal, 2012)
Ruthenium (II)- polypyridy1 complexes of similar size but with variable reduction potential undergo efficient photoinduced electron- transfer reactions with phenolate ions in aqueous medium. All these reactions are exergonic and are in accordance with the Marcus theory of electron transfer. At high negative ïƒªG° Marcus inverted region is observed in this bimolecular photoinduced charge separation reaction. <!--EndFragment-->